This question as written can be taken two ways: 9m + 6n - 3m + 7n = 6m + 13n, or (9m + 6n) - (3m + 7n) = 9m + 6n - 3m - 7n = 6m - n
9m + 9m + 3m + 3m = 24m
(9mX6m)2 2916m2 9mX(6m)2 324m3
4m + 9 + 5m - 12 = 42 9m -3 = 42 9m = 42 + 3 9m = 45 m = 5
4m + 9 + 5m - 5 = 42 9m + 4 = 42 9m = 38 m = 38/9
5 + 1 = 15m - 9m ie 6 = 6m so m = 1
This question as written can be taken two ways: 9m + 6n - 3m + 7n = 6m + 13n, or (9m + 6n) - (3m + 7n) = 9m + 6n - 3m - 7n = 6m - n
15m + 4 - 9m - 32 = 6m - 28
9m - 6m = 21 Combine like terms: 3m = 21 Divide both sides by 3: m = 7
9m + 9m + 3m + 3m = 24m
15m-9m = 6m simplified
If: 9m+2m = 33 Then: m = 3
9m
(9mX6m)2 2916m2 9mX(6m)2 324m3
m = 20/9 or 2 and 2/9
simplified it equals, 9m+8
-15 over 23